Doing Business in the Philippines 2011 - World Bank; International Finance Corporation (Washington, DC, 2017)
Doing Business in the Philippines 2011 is the second subnational report of the Doing Business series in the Philippines. In the first, Doing Business in the Philippines 2008, quantitative indicators on business regulations were analyzed for 21 cities in 3 regions: Luzon, the Visayas, and Mindanao. Doing Business investigates the regulations that enhance business activity and those that constrain it. Regulations affecting 3 stages of the life of a local business are measured at the subnational level in the Philippines: starting a business, dealing with construction permits, and registering property. These indicators were selected because they cover areas of local jurisdiction or practice. The indicators are used to identify business reforms and the extent to which these have been effective in simplifying the procedures, saving time, and lowering the cost of doing business. The data in Doing Business in the Philippines 2011 are current as of June 1, 2010.